Risk of Perioperative Respiratory Complications and Postoperative Morbidity in a Cohort of Adults Exposed to Passive Smoking. Issue 2 (February 2015) - Lee, Anna; Chui, Po Tong; Chiu, Chun Hung; Tan, Perpetua E.; Tam, Tsui Ping; Samy, Winnie; Tong, Patricia WY.; Critchley, Lester A. H.; Gin, Tony
Abstract : Objective: To evaluate the risks of perioperative respiratory complications and postoperative morbidity associated with active and passive cigarette smoking. Background: Environmental tobacco smoke is associated with perioperative respiratory events in children, but its effect in adults is unknown. Methods: We conducted a cohort study of 736 adult patients receiving general anesthesia for major elective surgery. Patients were classified according to their self-reported smoking history and urinary cotinine concentration within 48 hours before surgery. The main outcomes were composite measures of perioperative respiratory complications and postoperative morbidity on the third day after surgery. Results: There were 313 (42.5%) never-smokers (reference group), 92 (12.5%) passive nonsmokers, 157 (21.3%) ex-smokers without environmental tobacco smoke exposure, 53 (7.2%) passive ex-smokers, and 121 (16.4%) smokers. The incidence of perioperative respiratory complications and postoperative morbidity was 9.5% [95% confidence interval (CI), 7.5–11.8] and 29.2% (95% CI, 26.0–32.6), respectively. Smoking was significantly associated with an increased risk of perioperative respiratory complications [relative risk (RR), 4.40; 95% CI, 2.20–8.80] and postoperative morbidity (RR, 1.86; 95% CI, 1.22–2.83). Although passive smoking was not associated with the risk of perioperative respiratory complications, the risk of postoperative morbidity was increased in passive nonsmokers (RR, 1.51; 95% CI, 1.04–2.21) and passive ex-smokers (RR, 2.21; 95% CI, 1.39–3.50). Conclusions: One in 5 adults was exposed to environmental tobacco smoke before surgery. Passive cigarette smoking showed very little, if any, increased risk of perioperative respiratory complications. Both active exposure and passive exposure to cigarette smoke increased the risk of postoperative morbidity. Abstract : The risk of perioperative events associated with passive cigarette smoking was assessed. In this prospective cohort of 736 adults undergoing orthopedic surgery, general surgery, urological surgery, and cardiac surgery, passive smokers showed very little increased risk of perioperative respiratory complications. Both active smoking and passive smoking were associated with postoperative morbidity.